Biobanks – legal regulation and ethical challenges - Sadzevičius, Martynas; Mizeikis, Laimis (Vilnius University Open Series, 2024)
The establishment and development of biobanks in the context of biomedical research is an important transformational factor, enabling the collection of vast amounts of biological material, genetic information and clinical data. In recent decades, the role and technical capabilities of biobanks have evolved rapidly, giving rise to new ethical challenges. This paper discusses the legal regulation of biobanks both in Lithuania and internationally, focusing on ethical issues and interdisciplinary aspects of legal issues. An important legal issue in biobanking is the issue of a person’s consent to participate in biobanking activities. The traditional model of specific consent poses challenges due to the unknown nature of future research, and it is important to consider other alternatives such as broad, dynamic, and meta-consent models. Another important aspect is the return of health information to the biobank participant. The questions raised about disclosure, the definition of criteria and the differences between international and national legislation in this area show that the legal framework needs to be coherent and clear. In addition to the issues of personal consent, the study highlights the challenges of personal data protection. The GDPR establishes consent requirements, but biobanking activities require careful data security, especially in the context of research. Encryption of biomaterials is a way to ensure anonymity and the rights of participants, but it is important to balance this aspect with the biobank’s ability to carry out effective research. In summary, the legal issues surrounding biobanks include a range of ethical-legal challenges: the issue of consent to participate in a biobank, the issue of returning health information to the participant, and the issue of data protection for this personal data. The analysis of the information discussed in this paper reveals that successful regulation of biobanks must be consistent, respecting human rights and maximising the efficiency of research.